Friday, November 28, 2014

CSC 165 Computability, review

Week #12
Topic: computability, review

I really enjoyed learning about induction in a more sophisticated way. I always thought of induction as a process of going from a known case called base case to making generalizations that involve n and n+1 cases. The approach taken in class to prove statements by using the induction method made me fully understand how this method works.
I tried some somehow complex examples involving induction to reaffirm my knowledge.

Prove for all positive integers n, that 4n + 15n -1 is divisible by 9.

The first thing to notice in this exercise is that we are talking about positive integers which suggests that you should use induction to prove this statement.
As suggested in class, let’s start with the inductive step

Inductive Step
Assume 4n + 15n -1 is divisible by 9 # Induction hypothesis
We want show 4n + 1 + 15(n + 1) -1 is divisible by 9
4n + 1 + 15(n + 1) -1 = 4n + 1 + 15n + 15 -1
                                = 4n + 1 + 15n + 14
                                = (4n + 1 + 60n - 4) - 45n + 18           
                               # Manipulating the expression to use our induction hypothesis
                               ≡ 0 – 45n + 18 (mod 9)           # By induction hypothesis
                               ≡ 0 – 0 + 0         # 45n (mod 9) = 0 and 18 (mod 9) = 0

Since we did not notice any restriction on n, we can continue our induction process by establishing our base case.

Base Case
n = 1
4n + 15n -1 = 4(1) + 15(1) -1 = 18 ≡ 0(mod 9)


Another interesting induction problem is the following

Recall that {Fn}, the Fibonacci sequence, is defined by F1 = 1, F2 =1, and Fn = Fn – 1 + F n – 2 . Let r be a positive constant that satisfies the property that r2 = r + 1. Prove that  rn = Fn r + Fn – 1 .

Inductive Step
Assume rn = Fn r + Fn – 1 .     # Induction hypothesis
We want show rn + 1 = Fn + 1 r + Fn
rn + 1 = rn * r = (Fn r + Fn – 1) r         # By Induction hypothesis
          = (Fn r + Fn +1 - Fn ) r # Fn – 1  = Fn +1 - Fn
               = Fn r2 + Fn +1 r - Fn r
          = Fn +1 r + (Fn r2 - Fn r)
          = Fn +1 r + (Fn (r2 - r))
          = Fn +1 r + Fn      # r2 = r + 1

Here we notice that for the Fibonacci formula to work we need at least two elements. Therefore, we structure our base case as follows:

Base Case
n = 2
r2 = F2 r + F1
r2 = r + 1

Overall, it was a very good experience to do these SLOGS. Moreover, these posts helped me to reaffirm my knowledge and to increase my confidence when dealing with the material learned. Also, I really enjoyed learning all the topics taught in CSC165 and I hope that I will find more opportunities to apply math in Computer Science in upper years.


No comments:

Post a Comment